Material Selection and Evaluation of Supply Processes in Costume Design Applications: A Research on Fashion Design Students - Fatma Koc; Nisa Nur Duman (European Scientific Journal, ESJ, 2020)
The aim of this study is to determine whether the factors affecting the materials selection and supply processes of fashion design students in their costume design applications and the differences in the students' views on the selection and supply of materials used in their courses are different according to the types of schools. The population of the research consists of students studying at the undergraduate level in the Department of Fashion DesignFashion and Textile Design-Textile and Fashion Design in Turkey and its sample consists of 368 students studying in the Departments of Fashion Design-Fashion and Textile Design-Textile and Fashion Design for the 2017- 2018 academic year. The data of the measurement tool applied to the sample of the study was analyzed using the statistical package program “SPSS 25”. The frequency and percentage values of the data were determined and the relationship between the type of school where the students received education and their views on material selection and supply was analyzed at P<0.05 significance level by applying t-test. According to the results of the research, the students who studied fashion design had different views on the choice and supply of materials according to the type of school they studied. It was determined that the students studying at the foundation university know where they can obtain the materials at the best price compared to the students studying at the state university and that they experience fewer problems with the supply of materials.